Tuberculum sellae meningiomas - Calatroni, Maximiliano (Journal of Neurosurgery Academy, 2025)
This case report describes a 65-year-old female with tuberculum sellae meningioma presenting with progressive visual impairment. A pterional craniotomy with extradural anterior clinoidectomy enabled tumor resection and optic nerve decompression. Microsurgical techniques achieved gross-total resection without vascular complications. This report highlights the surgical nuances and importance of early optic nerve decompression for skull base neurosurgeons managing complex meningiomas.